If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3h = h + 6 Reorder the terms: 3h = 6 + h Solving 3h = 6 + h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1h' to each side of the equation. 3h + -1h = 6 + h + -1h Combine like terms: 3h + -1h = 2h 2h = 6 + h + -1h Combine like terms: h + -1h = 0 2h = 6 + 0 2h = 6 Divide each side by '2'. h = 3 Simplifying h = 3
| 6p+32-4p=22 | | 2d+c+4=0 | | 15x+3=3(5x+1) | | 5(3x+1)=15x | | 5x-6=12(0.75x-0.3)+10 | | 5x-14=16+10x | | x^2-6x+3y+6=0 | | .09x+.12*5=.10(x+5) | | (8w+17)(11w-23)=0 | | u^2+2-30=0 | | 20=2(2w+w-2) | | x^2+26x+27=0 | | 7+4(0.5+3x)=-15 | | 12+8y-7y=25 | | (-8x^2y)(x^9y^8)= | | (-8x^2y)(x^9y^8)=-8x^11y^9 | | 3(x-2)-4=2 | | -10.3=7.5+2v | | -(-1+7x)-6(-7-x)=36 | | 5x-3=4(x+8)-10 | | y^5-5y^2=0 | | 4w=77.2 | | 2(4x+28)=16 | | 3842=12(-8+5f) | | 450=-75p | | (x-2+3i)(x-2-3i)= | | k-8.4=-3.1 | | 24x-4x=12+4x | | 9y-18y=11-(14y+19) | | 9x+.12*5=.10(x+5) | | 4y-3+2y=6y+8-y | | 6x-3+4x=13 |